Address Presenting the Seventh Annual Report - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, described the lending approach of the Bank to various countries in the World. He discussed the proposed International Finance Corporation as a useful instrument for stimulating investment of private capital, both domestic and foreign, in enterprises significant in economic development. He spoke about sending general survey missions, composed of impartial experts, to help countries assess their potentialities and to draw up broad programs which will best channel their own energies and resources into development. He discussed development of water resources of the Indus River. He commented on the Schuman Plan for coal and steel in Europe. He concluded by saying that Bank has a vital role to play in development.